Students’ perception, knowledge, attitude and behaviour towards halal food products in Malaysia - A., Azlan (Rynnye Lyan Resources, 2022)
The perception, knowledge, attitude, and behaviour of Muslims are important in determining their purchasing behaviour of halal food products. This study exclusively focused on the purchasing behaviour of young Muslim university students who live independently and hold their purchasing power. The main objective of this study is to investigate the perception, knowledge, attitude, and behaviour of university students towards halal food products in Malaysia. This study has adopted the framework based on Ajzen’s Theory of Planned Behaviour (TPB) that hypothesized three determinants of behavioural intention; attitude, subjective norms and perceived behavioural control with the addition of two other variables; religiosity and ambience. This study has found that all the TPB determinants attitude (r = 0.187, p<0.05), subjective norms (r = 0.266, p<0.01), perceived behavioural control (r = 0.336, p<0.01) including the other two additional; religiosity (r = 0.245, p<0.245) and ambience (r = 0.254, p<0.01) were positively and significantly associated with purchasing intention of halal food products among the students. This study also revealed that families and media play an important role in introducing halal food products to these young consumers. Therefore, it was suggested that the authorities create a positive social norm on halal products among society.